REFORMULATION OF THE CONCEPT OF JUDICIAL ACTIVISM THROUGH LEGAL DISCOVERIES AND BREAKTHROUGHS AFTER THE NATIONAL CRIMINAL CODE AS AN EFFORT TO BALANCE THE PRINCIPLE OF LEGAL CERTAINTY AND SUBSTANTIVE JUSTICE - Entang Nuryanto; Prija Djatmika; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
Certainty law as fundamental principles of the Indonesian state of law are often face tension with demands justice substantive in practice justice criminal law , especially in the middle dynamics social and developmental type crimes that are not fully accommodated by law positive . Condition the push emergence practice judicial activism as response on limitations of written norms , in particular through invention law ( rechtsvinding ) and breakthrough legal breakthrough . Although​ get legitimacy juridical through Constitution Power National Judiciary and Criminal Code, practice judicial activism Not yet accompanied by clear settings​ about its limitations and parameters , so that potential cause uncertainty law , inconsistency decision , and exceedance authority judicial . This article aim For analyze typology form judicial activism carried out by judges in practice justice Indonesian criminal law and formulate a reformulation model draft ideal judicial activism to balance principle certainty law and justice substantive in implementation of the National Criminal Code. Research This use method juridical normative with approach legislation and approaches conceptual , through analysis to regulation legislation , jurisprudence , and doctrine law . Research results show that judicial activism in practice justice criminal present in three typology main , namely through method interpretation law , construction law , and breakthroughs law that goes beyond normative limits . This article propose a reformulation model judicial activism based seven fundamental parameters that are hierarchical and cumulative . This model expected capable give corridor clear normative​ for judges to engage in judicial activism still measurable , accountable , and non- shift become arbitrariness judicial , at the same time ensure realization balance between certainty law and justice substantive in system justice Indonesian criminal law .